Posted by Blue on Saturday, October 8, 2011 at 7:38pm.
factor the bottom
factor the top with (x-3) a factor so we can cancel it
(x-3)(x+b) = x^2+x+c
x^2 - 3x +b x - 3 b = x^2 + x + c
b x -3 x = x so b = 4
then c = -12
(x^2 + x - 12)/(x^2 - 5 x + 6)
(x-3)(x+4) / [(x-3)(x-2)]
when x = 3
7/1 = 7
hmmm. looks familiar. Anyway,
denominator is (x-3)(x-2), so we want the top to be
(x-3)(x-k) so that the fraction exists everywhere except at x=3, but has a finite limit there.
x^2 - (k+3)x + 3k = x^2 + x + c
k+3 = -1
k = -4
so c = 3k = -12
x^2 + x + c = x^2 + x -12 = (x-3)(x+4)
CALCULUS - need help! - Determine the limit of the trigonometric function (if it...
Calculus - If f(x) and g(x) are differentiable and lim(x->a) f(x)/g(x) ...
Calculus - Find a value of the constant k such that the limit exists. lim x-&...
Calculus - Find the following limits algebraically or explain why they don...
Calculus - Got a midterm worksheet. Realized how confused I am. Here are some ...
calc - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- ...
Calc. Limits - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/...
Calc Please Help - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I ...
Calculus - Evaluate each limit. If it exists. a) Lim x^3 + 1 x->1...
math - i need some serious help with limits in pre-calc. here are a few ...
For Further Reading